ترقية مهارة الكلام بطريقة القصص بحث صفي إجرائي لدى طلاب الصف الثاني للمتوسطة بمعهد الإمام النووي رنتو برابات - Maghfirah, Lailatul; Fakhrurrazi, Fakhrurrazi; Lubis, Arbonas (Lembaga Yasin AlSys, 2024)
The research aims to improve the speaking skill using the story method, a procedural classroom research among second-year middle school students at the Imam Nawawi Rentu Prabat Institute. Use this type of data collection method because observations, numbers, and opinions related to a particular phenomenon or problem are not the type of data collection method. This type of research is an action classroom research with two cycles consisting of two meetings in one cycle, each cycle consisting of: planning, implementation, monitoring and reflection. The research population means students in the second year of middle school at Imam Nawawi Rinto Prabat Institute, numbering 35 students. The method used by the researcher is the total sampling method. . The results showed that with the story method there was a pleasant atmosphere so that the learning results of the students increased, that is, from the results of the first cycle to the second cycle there was an increase. In the first cycle the number of students who obtained perfect grades was 11 students or 31%. Incomplete grades were in The first cycle 24 students or 69%, while in the second cycle there was an increase in complete grades to 30 students or 86%, and incomplete grades in the second cycle students 5 or 14%, an increase of 55%. It was found that the story method can improve the learning outcomes of speaking Arabic among eighth grade students at Imam Nawawi Islamic Boarding School Rantau Prabat.